Negative Effects of Pollen Drought Stress on Floral Volatiles, Floral Nectar, Pollinator Behavior, and Seed Production in Ocimum basilicum Plants - Naira Nayab; Md Anzer Alam (Tunisian Journal of Plant Protection)
Nayab, N., and Alam, M.A. 2023. Negative effects of pollen drought stress on floral volatiles, floral nectar, pollinator behavior, and seed production in Ocimum basilicum plants. Tunisian Journal of Plant Protection 18 (2): 41-61.